PENGARUH PENDIDIKAN DAN TINGKAT PENGANGGURAN TERHADAP KEMISKINAN DI SUMATERA BARAT - Daffa Febri Nurdinda; Fira Mutawaqila; Intan Wahyu Wanti; Indri Puspita Sari; Muhammad Roofi; Ansofino (STKIP Subang, 2026)
Poverty remains one of the major development challenges influenced by various factors, including the level of education and unemployment. Education plays a crucial role in improving the quality of human resources, thereby creating greater employment opportunities and increasing income, while a high unemployment rate reduces people's ability to meet their basic needs and may lead to higher poverty levels. This study aims to analyze the effect of education and unemployment on poverty in West Sumatra Province. The research employs a quantitative approach using multiple linear regression analysis. The data used are secondary data obtained from the Central Statistics Agency (BPS) of West Sumatra, covering educational indicators, the Open Unemployment Rate (OUR), and the poverty rate. The results indicate that education has a negative and significant effect on poverty, whereas unemployment has a positive and significant effect on poverty. Simultaneously, education and unemployment significantly influence poverty in West Sumatra Province. These findings suggest that improving the quality of education and reducing unemployment through the expansion of employment opportunities are essential strategies for alleviating poverty and enhancing the welfare of the people in West Sumatra.